Muscle functional characteristics of Latvian weightlifters in lightweight categories - Čupriks, Leonīds; Ciematnieks, Uģis; Knipše, Gundega; Čuprika, Aleksandra; Lesčinskis, Māris; Saulīte, Sergejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
To predict the potential physical abilities of weightlifters, it is recommended to follow the complex methodology for assessing the weightlifter in certain weightlifting competition exercise. Our aim of the study was to investigate the muscle contraction and relaxation process of Latvian weightlifters of lightweight categories (-56kg, -62kg) in the competition-like situation. Tests were conducted on a dynamometer system REV9000 using leg flexion and extension in knee joint. Establishing the contraction and relaxation processes of weightlifters nerve muscle apparatus in electromiograhical curves allowed us to clear out five main muscle contraction and relaxation interactional patterns: athletes straining muscles very quickly with very fast relaxation, athletes strain and relax their muscles relatively fast; athletes straining muscles fast with slow relaxation , slowly straining the muscles with quick relaxation, slowly contracting the muscles and slowly relax them. Latvian weight lifters training process requires further attention in improvement of muscle relaxation and tightening processes with selection of appropriate training resources and means.